MODULATION OF MOTOR CORTICES ON MANUAL ASYMMETRIES (Kinesiology, 2022)
Differences between hands in motor performance are associated with differences in the interaction of inhibitory connections of homologous parts of the cerebral hemispheres. Modulation of these inhibitory connections in the right and left primary motor cortex (M1) may alter manual performance asymmetries. To investigate this assumption, eleven right-handed male university students performed a discrete aiming task in a digitizing tablet under three experimental conditions: dominant M1 inhibition, non-dominant M1 inhibition, and sham. The Transcranial Direct Current Stimulation technique was used to increase or decrease participants’ M1 excitability. We used a within-subject design, in which we counterbalanced the order of conditions and the order of the starting hand among participants. The performance-dependent variables were: reaction time, movement time, and radial error, while kinematic variables were: peak velocity, relative time to peak velocity, and number of discontinuities in acceleration in the final homing phase. Results showed changes in asymmetry related to reaction time, movement time, and relative time to peak velocity. The interaction between M1 modulation and hemispheric specialization produced specific changes in these variables. Taken together, these findings revealed that modulation of the dominant and non-dominant M1 affects manual performance asymmetries.Key words: handedness, hemispheric specialization, transcranial direct current stimulation (tDCS), aiming task